Sensitivity to temporal fine structure and hearing-aid outcomes in older adults - Perez Vallejos, Elvira; Mccormack, Abby; Edmonds, Barrie (Frontiers in Neuroscience, 2014)
Objective: To investigate the effect of sensitivity to temporal fine structure (TFS) on subjective measures of hearing aid outcome. Design: Prior to receiving hearing aids, participants completed a test to assess sensitivity to TFS and two self-assessment questionnaires; the Glasgow Hearing Aid Benefit Profile (GHABP), and the Speech, Spatial and Qualities of hearing (SSQ-A). Follow-up appointments, comprised three self-assessment questionnaires; the GHABP, the SSQ-B, and the International Outcome Inventory for Hearing Aid Outcomes (IOI-HA). Study sample: 75 adults were recruited from direct referral clinics. Results: Two thirds of participants were found to have good sensitivity to TFS; listeners with good sensitivity to TFS rated their hearing abilities higher at pre-fitting (SSQ-A) than those with poor sensitivity to TFS. At follow-up, participants with good sensitivity to TFS showed a smaller improvement on SSQ-B over listeners with poor sensitivity to TFS. Among the questionnaires, only the SSQ showed greater sensitivity to measure subjective differences between listeners with good and poor sensitivity to TFS. Conclusions: The clinical identification of a patient's ability to process TFS information at an early stage in the treatment pathway could prove useful in managing expectations about hearing aid outcomes.